2021
DOI: 10.1590/1516-3180.2020.0411.r1.18112020
|View full text |Cite
|
Sign up to set email alerts
|

Physician and patient-related factors associated with inappropriate prescribing to older patients within primary care: a cross-sectional study in Brazil

Abstract: BACKGROUND: Physician and patient-related characteristics can influence prescription of medications to older patients within primary healthcare. Use of Brazilian criteria may indicate the real prevalence of prescription of potentially inappropriate medications to this population. OBJECTIVES: To evaluate prescription of potentially inappropriate medications to older patients within primary care and identify patient-related and prescribing physician-related factors. DESIGN AND SETTING: This cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
7
0
4
Order By: Relevance
“…A recent systematic review focused on non-clinical programs to reduce the inappropriate or unnecessary use of medicines observed that interventions consisting of education messages and recommended behavior alternatives were more likely to be successful in reducing the inappropriate use of medicines or medical procedures ( Lin et al, 2020 ). Educational strategies are essential to improve prescription, as observed by Amorim et al (2021) since physician-related characteristics can influence the number of PIM prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review focused on non-clinical programs to reduce the inappropriate or unnecessary use of medicines observed that interventions consisting of education messages and recommended behavior alternatives were more likely to be successful in reducing the inappropriate use of medicines or medical procedures ( Lin et al, 2020 ). Educational strategies are essential to improve prescription, as observed by Amorim et al (2021) since physician-related characteristics can influence the number of PIM prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…While the debate continues around the distinction between appropriate and inappropriate polypharmacy, this well-established link between polypharmacy and PIMs suggests even considered polypharmacy may contain specific drug–drug or drug–disease interactions that are suboptimal. Of interest, only a handful of studies that focused on measuring associations with PIMs provided a detailed definition of polypharmacy; 28 , 45 , 52 , 64 , 66 however, it remains unclear whether associations vary between doctor-prescribed and self-prescribed medicines. The relationship between education and PIMs use appears to have been less extensively researched, relative to the polypharmacy literature ( Table 12 ).…”
Section: Omitted Medicines (Underprescribing)mentioning
confidence: 99%
“…10 Para além da polifarmácia e idade avançada, o sexo feminino associa-se frequentemente a PIM, assim como, em menor escala, a história pessoal de depressão ou o baixo nível socioeconómico. 5 As comorbilidades também contribuem para o aumento da vulnerabilidade do idoso à iatrogenia, uma vez que, se por um lado aumentam a probabilidade do doente estar polimedicado, aumentando o risco de interações fármaco -fármaco, por outro também influenciam a farmacocinética, aumentando o risco de interações doença -fármaco. 10…”
Section: Fatores De Risco Para Iatrogeniaunclassified
“…Estão frequentemente associados a reações adversas como quedas, hemorragias gastrointestinais ou delírio, assim como aumento dos internamentos hospitalares e maior morbimortalidade. 5,6 Podem ser definidas cinco categorias para os medicamentos associados a PMI: os que induzem alterações psicológicas; os que afetam a função renal; os que são inapropriados devido às interações medicamentosas que provocam; os que não podem ser usados em determinadas condições de morbilidade e os que necessitam de ajustes de dosagem. 3 Nos Estados Unidos, existirão todos os anos cerca de 180 000 eventos adversos relacionados com medicação, fatais ou quase fatais, em maiores de 65 anos, sendo que, pelo menos metade destes, serão evitáveis.…”
Section: Introductionunclassified